Montserrat's backyard agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Since the onset of volcanic activity on the island of Montserrat in the Caribbean, residents and particularly farmers have been forced to engage themselves in backyard gardening, currently the key production pattern. With the volcanic crisis, the...